Simulation of power distribution management system using OMACS metamodel - Manghat, Jaidev (Kansas State University, 2008)
Designing and implementing large, complex and distributed systems using semi-autonomous agents that can reorganize and adapt themselves by cooperating with one another represents the future of software systems. This project concentrates on analyzing, designing and simulating such a system using the Organization Model for Adaptive Computational Systems (OMACS) metamodel. OMACS provides a framework for developing multiagent based systems that can adapt themselves to changes in the environment. Design of OMACS ensures the system will be highly robust and adaptive. In this project, we implement a simulator that models the adaptability of agents in a Power Distribution Management (PDM) system. The project specifies a top-down approach to break down the goals of the PDM system and to design the functional role of each agent involved in the system. It defines the different roles in the organization and the various capabilities possessed by the agents. All the assignments in PDM system are based on these factors. The project gives two different approaches for assigning the agents to the goals they are capable of achieving. It also analyzes the time complexity and the efficiency of agent assignments in various scenarios to understand the effectiveness of agent reorganization.
Keywords: Simulation; Multiagent system; OMACS metamodel; Organization; Computer Science (0984)